Redescription of Lophiodes infrabrunneus Smith and Radcliffe, 1912, a senior synonym of L. abdituspinus Ni, Wu and Li, 1990 (Lophiiformes: Lophiidae) - Ho, Hsuan-Ching; Séret, Bernard; Shao, Kwang-Tsao (Zootaxa, 2009)
Lophiodes infrabrunneus Smith and Radcliffe, 1912 is redescribed on the basis of all known specimens. The species is redefined as: a species of Lophiodes with three dorsal spines, postcephalic spines absent; illicium relatively short, 13.3– 24.2% of SL; second and third dorsal spine relatively short, 12.2–21.2% and 9.1–20.6% of SL respectively, a narrow leaf–like flap, and tendrils present on second and third dorsal spine. Lophiodes abdituspinus is a junior synonym of L. infrabrunneus based on examination of type series of both species. L. infrabrunneus is distributed from Japan, to the Timor Sea, Salomon Is. and northwestern Australia, in eastern Indian Ocean where it occurs in depths between 208–1412 m.